A microporous titanosilicate for selective killing of HeLa cancer cells - Ferdov, Stanislav (2013)
Structural distribution of zinc(II) ions in the pore system of three silicate molecular sieves has revealed an unprecedented application of the microporous titanosilicate Zn-ETS-4 as a non toxic, highly efficient and selective inhibitor of HeLa cancer cells.